Towards a process for advancing women in coaching through mentorship - Banwell, J.; Stirling, A.; Kerr, G. (International Journal of Sports Science & Coaching, 2019)
Female coaches continue to be underrepresented in the coaching domain despite remarkable strides made in female athlete participation. To develop, support, and advance female coaches, mentorship initiatives have been widely recommended. Positive outcomes have been reported in nonsport literature for the professional advancement of women through mentorship, but far less attention has been paid to the advancement of female coaches through mentorship in sport. This study used a multi-methods methodology to explore female coaches` experiences in, and outcomes of, a female coach mentorship program. Survey data and individual in-depth semi-structured interviews with participating mentor (n = 7) and mentee coaches (n = 8) from the program were conducted. Survey data were analyzed descriptively and the interview data were analyzed using an inductive thematic analysis. Findings revealed two primary forms of mentoring support provided through the mentorship program that facilitated personal and professional outcomes for participating mentor and mentee coaches, as well as various quality attributes of the mentorship process. Based upon these findings, a mentorship model for advancing women in coaching is proposed.